Applying the technique of guessing word meanings from context for 11th form students at Le Loi high school. M.A Thesis Linguistics: 60 14 10 - Lê, Thị Thủy (University of Languages and International Studies, 2017)
M.A. Thesis. English Linguistics Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013